Analisis Hukum Islam Terhadap Pembulatan Tarif Layanan Jasa Transportasi KOPADA TAKSI Di Purworejo - Muhajir Muhajir; Muhammad Agus Galih Wicaksono (Universitas Cokroaminoto Yogyakarta, 2021)
This research aims to answer the problem, How is the Analysis of Islamic Law on the Minimum Distance Limitation of the Tariff for Kopada Taxi Purworejo Transportation Services. This type of research is field research (field research) using a qualitative descriptive approach, which describes conditions, situations, or phenomena about the data obtained, namely about the rounding of taxi fares in Purworejo. Then it is analyzed using an inductive thinking pattern, namely by first explaining the facts that occur in the field after which it is connected to the contract theory and the theory of ijarah. Dimna Kopda taxis in Purworejo made an agreement with drivers / drivers that drivers / drivers are prohibited from asking for more than passengers. However, in practice there are drivers / drivers who still ask to pay more than the tariff to the pemunpang. The results of the study concluded that, the practice of rounding up the taxi Kopda fare in Purworejo has met the pillars and requirements of ijarah, although in practice the rounding of tariffs carried out by drivers / passengers makes passengers less willing to round the tariff and feel compelled to pay more than what has been done. mentioned on the meter.